2010
DOI: 10.3389/fpsyt.2010.00011
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive disorders are associated with different patterns of brain asymmetry than normal aging: the PATH through life study

Abstract: Background and Purpose: Defining how brain structures differ in pre-clinical dementia is important to better understand the pathological processes involved and to inform clinical practice. The aim of this study was to identify significant brain correlates (volume and asymmetry in volume) of mild cognitive disorders when compared to normal controls in a large community-based sample of young-old individuals who were assessed for cognitive impairment. Methods: Cortical and sub-cortical volumes were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
4
39
1
Order By: Relevance
“…Such effects should be further investigated in future studies because the left and right hemispheres have been reported to differ in their vulnerability to AD neurodegenerative processes, which tend to start earlier and progress faster in the left hemisphere. 37,38 The prevalence of SMD in the present sample was similar to rates reported in the literature for epidemiological samples with 23% reporting SMD at baseline and 18% at follow-up. 3,23 Because individuals with dementia, MCI, or neurological disorder were excluded, SMD was not associated with pre-existing clinical disorders.…”
Section: Discussionsupporting
confidence: 90%
“…Such effects should be further investigated in future studies because the left and right hemispheres have been reported to differ in their vulnerability to AD neurodegenerative processes, which tend to start earlier and progress faster in the left hemisphere. 37,38 The prevalence of SMD in the present sample was similar to rates reported in the literature for epidemiological samples with 23% reporting SMD at baseline and 18% at follow-up. 3,23 Because individuals with dementia, MCI, or neurological disorder were excluded, SMD was not associated with pre-existing clinical disorders.…”
Section: Discussionsupporting
confidence: 90%
“…This phenomenon could have theoretically impacted our results, even though our hippocampal indices were derived from automated segmentation, since the initial training set was developed through manual tracing. Although these results remain incompletely understood, they raise the possibility that the interactions between hippocampal volume and other AD biomarkers and risk factors may not always be bilaterally symmetric, particularly since greater hemispheric asymmetry in hippocampal volumes is associated with a higher likelihood of cognitive impairment [47]. …”
Section: Discussionmentioning
confidence: 99%
“…These fibers (CC6L) are indeed originating from the left temporo-parietal GM, which is primarily affected in the early stages of AD [21], [36], [52], [53].…”
Section: Discussionmentioning
confidence: 99%